Relationship between blood glucose levels and diabetic neuropathy examination score in patients with diabetes mellitus - Singarayar, Eunice Keren; Josephrajan, Tamilarasan Anthoni; Jayabalan, Prakash (International Journal of Research in Medical Sciences, 2025)
Background: Diabetic neuropathy is a specific type nerve damage that primarily affects the peripheral nervous system, causing a loss of sensation in the extremities, disruption of autonomic functions, and to a lesser extent, motor function. The length of time a person has diabetes and their haemoglobin A1C (HbA1C) levels (a measure of glycated haemoglobin which reflects average daily glucose levels) are significant factors in determining the development of diabetic neuropathy. Methods: This was a cross-sectional study conducted between April 2023- July 2023 among 51 participants who met the selection criteria participated in the study and were assessed using the Diabetic Neuropathy Examination Score (DNE score). Results: The study concluded that the symptoms of diabetic neuropathy in high blood sugar individuals are higher in males (59%) than females (41%) due to changes in blood sugar levels. A direct correlation found amidst blood glucose volume and diabetic neuropathy examination (DNE score). Conclusion: Hence the study concluded that the symptoms of glycated haemoglobin neuropathy in diabetes patients are higher in males (59%) than females (41%) due to changes in blood sugar levels.